2001
DOI: 10.1046/j.1440-1703.2001.00432.x
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific variation and ontogenetic change in antiherbivore defense in myrmecophytic Macaranga species

Abstract: The present study examined whether or not coexisting congeneric plant species have different defense strategies against herbivores, and the intensity of defense changes ontogenetically. We focused on nine myrmecophytic Macaranga species and estimated the intensity of non‐biotic and biotic defense by the degree of leaf damage in ant‐free and ant‐occupied plants, respectively. Ant colonization of myrmecophytic Macaranga species occurred in the early stage of plant development (5–50 cm‐tall seedlings). Following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 38 publications
(54 reference statements)
1
26
0
2
Order By: Relevance
“…The benefits conferred to partner species in ant‐plant mutualisms can vary both spatially and temporally (Horvitz & Schemske 1990; Alonso 1998; Bronstein 1998; Kersch & Fonseca 2005). Our results and those of others indicate that a full appreciation of these benefits requires a broad perspective in which one considers how plant age (Itino & Itioka 2001; Nomura et al . 2001; Del Val & Dirzo 2003), local environmental conditions (Folgarait & Davidson 1995; Heil et al .…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The benefits conferred to partner species in ant‐plant mutualisms can vary both spatially and temporally (Horvitz & Schemske 1990; Alonso 1998; Bronstein 1998; Kersch & Fonseca 2005). Our results and those of others indicate that a full appreciation of these benefits requires a broad perspective in which one considers how plant age (Itino & Itioka 2001; Nomura et al . 2001; Del Val & Dirzo 2003), local environmental conditions (Folgarait & Davidson 1995; Heil et al .…”
Section: Discussionsupporting
confidence: 72%
“…That young myrmecophytes may have increased chemical defences prior to ant colonization is a logical extension of current plant defence theories (Heil & McKey 2003; but see Boege & Marquis 2005), but evidence supporting this idea remains equivocal (Itino & Itioka 2001; Nomura et al . 2001; Del Val & Dirzo 2003).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…). The extent of protection provided by ants appears to be a function of plant size, ant species and herbivore behavior (Madden and Young , Itino and Itioka , Trager and Bruna , Llandres et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, this may affect the levels of damage suffered by plants as they develop and the selective potential of herbivores. Several studies have reported ontogenetic differences in herbivore preference for particular plant stages (Tahvanainen et al 1985;Jogia et al 1989;Fenner et al 1999) and in herbivore damage (Zagory and Libby 1985;Hanley et al 1995;Fritz et al 2001;Itino and Itioka 2001). Few studies, however, have evaluated whether such differences are promoted by changes in plant quality as food for herbivores, and/or by changes in the risk of predation that herbivores face while feeding on plants at different ontogenetic stages (Kearsley and Whitham 1989;del-Val and Dirzo 2003).…”
Section: Introductionmentioning
confidence: 99%